Crednerite CuMnO2 as highly efficient Fenton-like catalysts for p-nitrophenol removal:Synergism between Cu(I) and Mn (III). (15th October 2021) - Yin, Chuankun; Zhou, Siji; Zhang, Keyi; Bai, Jiale; Lv, Yangyang; Zhang, Xuewen; Li, Xiaoxia; Xu, Aihua
Abstract: p-Nitrophenol (PNP) is one of the highly toxic and mutagenic pollutants existed in aquatic environment. In this work, the crednerite CuMnO2 nanoflake was prepared and used to degrade PNP with peroxymonosulfate (PMS) as the oxidant. It was found that CuMnO2 exhibited much higher activity than other Cu-based catalysts such as CuO, Cu2 O, CuFe2 O4 and CuFeO2, with 90% of PNP degraded after 10 min under mild reaction conditions. The catalyst was also stable during five successive runs. Sulfate and hydroxyl radicals produced from PMS reduction by Cu(I) species, as well as superoxide ions and single oxygen, contribute to the degradation of PNP. More importantly, the interactions between Mn and Cu species in CuMnO2 were identified by X-ray photoelectron spectroscopy (XPS), fourier transform infrared spectroscopy (FT-IR) and linear sweep voltammetry (LSV), and were further confirmed by the control experiment with the mixture of Cu2 O + Mn2 O3 . The results implied that the high valent Mn(III) species acted as Lewis acids to withdraw electron from PMS, resulting that the Cu(I) species can be easier oxidized to Cu(II) by PMS with the formation of radicals. These findings provide an ideal bimetallic heterogeneous catalyst and a new mechanism for PMS-mediated reaction. Graphical abstract: Image 1 Highlights: Crednerite CuMnO2 was prepared by a simple hydrothermal method. The catalyst showed high activity for PNP degradation via PMS activation. CuMnO2 was excellently reusability during consecutive cycles. A synergistic effect between Cu(I) and Mn(III) was confirmed. Possible degradation mechanism of PNP was proposed.